2017
DOI: 10.1073/pnas.1609579114
|View full text |Cite
|
Sign up to set email alerts
|

Perplexing cooperative folding and stability of a low-sequence complexity, polyproline 2 protein lacking a hydrophobic core

Abstract: The burial of hydrophobic side chains in a protein core generally is thought to be the major ingredient for stable, cooperative folding. Here, we show that, for the snow flea antifreeze protein (sfAFP), stability and cooperativity can occur without a hydrophobic core, and without α-helices or β-sheets. sfAFP has low sequence complexity with 46% glycine and an interior filled only with backbone H-bonds between six polyproline 2 (PP2) helices. However, the protein folds in a kinetically two-state manner and is m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(77 citation statements)
references
References 72 publications
8
69
0
Order By: Relevance
“…Instead, this protein with 46 glycine residues forms stable bundles of pPII helices connected by HBs. The authors attributed this peculiar fold to the high level of pPII dihedral angle bias [92], which is consistent with findings reported here.…”
Section: Discussionsupporting
confidence: 92%
“…Instead, this protein with 46 glycine residues forms stable bundles of pPII helices connected by HBs. The authors attributed this peculiar fold to the high level of pPII dihedral angle bias [92], which is consistent with findings reported here.…”
Section: Discussionsupporting
confidence: 92%
“…Indeed, packing interactions within the hydrophobic core can have a marked effect on the stability of a protein domain, 13 although there are noteworthy examples of protein stability without a hydrophobic core. 14 Here, we demonstrated that the calcium-binding fold was sensitive to the 'hydrophobicity' of the solvent and that an EGF-like peptide with a richer core was more structurally stable.…”
Section: Discussionmentioning
confidence: 84%
“…[C] increases, so that at high [C], the statistical properties of the denatured state ensemble (DSE) of globular proteins and IDPs, such as R g , would exhibit the scaling R g ≈ 0.20N ν T , with ν ≈ 0.588. 81 Because the R g scaling of DSEs of globular proteins at high denaturant concentrations is statistically equivalent to those for IDPs (hence the plausible relevance of IDPs to the SAXS-FRET controversy), it is not surprising that the optimal values for the SOP-IDP model (Eq. 3) differ from the [C] = 0 values.…”
Section: Methodsmentioning
confidence: 99%